Kepastian Hukum Bagi Nasabah Yang Mengalami Pemblokiran Sepihak Oleh Bank - Rahmadi Indra Tektona (Fakultas Hukum Universitas Mulawarman, 2019)
Banks in blocking accounts must be based on the applicable laws and regulations to maintain the trust of customers. Banks as financial service institutions should always follow the existing account blocking procedures and have been regulated in the prevailing laws and regulations so that errors do not result in losses for their customers. The mistake that can be detrimental to customers is unilaterally blocking accounts by the bank. This study aims to determine the form of legal protection for customers who experience unilateral account blocking, thereby resulting in the certainty of the right to unused customer funds. Based on the study results, it was found that customers can make Internal Dispute Resolution and External Dispute Resolution efforts to defend their rights when experiencing unilateral blocking by the bank.Keywords: Legal protection; account balance; blocking; customer; bank